Kehitysyhteistyön mieli ja mielettömyys Suomalaiset Apumaassa 1965-2000 - Kuhanen, Jan (Historiallisia Tutkimuksia, 2023)
The book approaches the history of Finnish development cooperation through the experiences of development aid workers. At its core is a small group of Finns (experts and officials from different fields) who have worked with international development aid in Asia, Africa and Latin America. Their memories and experiences, together with diverse archival material offer an interesting window into the world of development (cooperation), or "Aidland", from the 1960s to the turn of the millennium. The research focuses on the personal motives and experiences of Finnish aid workers from the 1960s to the 2000s. The book offers perspectives on the historical construction of Aidland since the 1940s and on the gradual integration of Finland and the Finns into its structures. It describes the mindset of the first two generations of aid workers and the factors that made them interested in developing countries. The book follows their education, their first contacts with Aidland, adaptation to work and conditions, returning home and the challenges that come with it. The study gives the reader a view of the power positions, hierarchies and contradictions in Aidland and development cooperation, which at times led Finns to reassess their motives and justify to themselves the meaningfulness of the entire undertaking. Through their experiences, the book also deals with the less-known side of development cooperation, such as corruption, prejudices, and opposition to development projects, as well as their occasionally unwanted consequences in partner/recipient countries. It also sheds light on the effects of the Aidland experience on an individual's worldview and identity. The book is an academic study suitable for a wide audience, from university students to ordinary readers interested in development cooperation. The book helps to understand both the history of development and the construction of multi-level connections of Finnish society with the countries of the Global South. It is therefore also ideally suited for readers interested in the development of Finland's internationalization in the late twentieth century. For its part, the book contributes to wider public debates on development cooperation.